2008
DOI: 10.1007/s00246-008-9328-7
|View full text |Cite
|
Sign up to set email alerts
|

Truncus Arteriosus: Diagnostic Accuracy, Outcomes, and Impact of Prenatal Diagnosis

Abstract: Limited data exist on the impact of prenatal diagnosis and outcomes of fetal truncus arteriosus (TA). We sought to assess prenatal diagnostic accuracy and prenatal outcomes in fetuses with TA and compare postnatal outcomes in neonates with prenatally and postnatally diagnosed TA. Records were reviewed for patients diagnosed with TA in utero or at ≤60 days of life from 1992 to 2007. Forty-three (32%) of 136 TA patients had prenatal diagnosis. Five patients with TA were prenatally misdiagnosed, and 5 with other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
56
5
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 15 publications
6
56
5
1
Order By: Relevance
“…Prenatal diagnosis of CAT remains challenging and is associated with a high rate of therapeutic elective termination [7]. Similarly, 8 out of the 17 pregnancies included in our study, were terminated through a therapeutic abortion, and probably those lost from our evidence reached the same course or died after birth.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Prenatal diagnosis of CAT remains challenging and is associated with a high rate of therapeutic elective termination [7]. Similarly, 8 out of the 17 pregnancies included in our study, were terminated through a therapeutic abortion, and probably those lost from our evidence reached the same course or died after birth.…”
Section: Discussionmentioning
confidence: 92%
“…According to a review which assessed the post-surgical evolution of CAT performed within the first months of life, only 28 out of 48 alive newborns with CAT survived [4], underlining that the diagnosis of CAT carries only approximately 50% survival chances. Another study pointed out a survival rate much lower, GA -gestational age (weeks); CAT -Common arterial trunk; *type 2 or 3 could not be correctly diagnosed in utero only 10% after surgical procedure for CAT [7]. The same study stated that even though the prenatal diagnosis led to a surgical repair at a younger age, the neonatal survival rate remained constant [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies examining the accuracy of prenatal diagnosis of CAT have been reported (78.6-95.8%) [2,3,4,5]. Although CAT can be diagnosed with a high degree of accuracy, it is sometimes difficult to make a diagnosis when only the single great vessel is identified by fetal echocardiography.…”
Section: Introductionmentioning
confidence: 99%